Teaching Life. The Education of a Modern Personality - Müller, Hans-Peter (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2019)
Georg Simmel was not an educator in the classical sense. But he had profound influence upon his students precisely because he was no educator. This paradoxical thesis is developed in three steps: First, Simmel’s basic problem is discussed with respect to his own personality: modernity and individuality; second his analysis on money and modern life is reconstructed; third, his views on education and instruction are outlined demonstrating his liberal principles of education. Taken together, these three steps demonstrate the educational charisma of Georg Simmel.